The Guarantee od Adopted Children on Their Inheritance through Wasiah Wajibah - Erkham Maskuri (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
This research examines the rules of law as a system-building related to a legal event which aims to give legal arguments as the basis for determining the right or wrong of a case according to a law perspective by referring to books of Fiqh and the compilation of Islamic law which contains regulation prevailing in Indonesia. This study discusses about the implementation of wasiah wajibah in Indonesia and the role of judges in deciding a case related to wasiah wajibah. This study uses the concepts of normative law approach with three criteria of law such as primary, secondary, and comparative laws by combining Wasiah Wajibah law in an Islamic perspective with the Islamic Law Compilation. The method of collecting the data used in this study is through library research and looking for law materials that are related and relevant to qualitative analysis. All collected data from various sources are arranged properly and then analysed using qualitative method so that it easily solve the problems. Research finding shows that wasiah wajibah is a solution for adopted children to obtain their rights to inheritance with certain provision and limit so that the judges have a way in deciding the case.